Design of wave-like dry friction and piezoelectric hybrid dampers for thin-walled structures. (17th February 2021) - Wu, Y.G.; Li, L.; Fan, Y.; Ma, H.Y.; Zucca, S.; Gola, M.
Highlights: A wave-like damper combining friction and piezo damping for thin-walled structures is proposed. It provides greater damping while less sensitive to the variation of the excitation level or the normal load. The nonlinear MEMCF is defined for electromechanically coupled systems with contact nonlinearities. Closed-from relation between the nonlinear MEMCF and the optimal shunted damping is established. A design flow based on the nonlinear modal analysis for wave-like hybrid dampers is proposed. Abstract: This paper proposes a wave-like hybrid damper containing both dry friction and piezoelectric damping mechanisms for thin-walled structures. The idea is to distribute piezoelectric material on the wave-like friction plate, so that the elastic deformation of the plate can be further utilized to generate additional shunted piezoelectric damping. The proposed damper has the following advantages: simple structure, easy installation and maintenance, convenient to adjust the normal preload, and feasible to mount piezoelectric materials. Combined with damped nonlinear normal modes (dNNMs), the nonlinear modal electromechanical coupling factor (nonlinear MEMCF) is proposed, and its relationship with piezoelectric damping is established for electromechanically coupled systems with contact nonlinearities. Based on the extended periodic motion concept (E-PMC) of dNNMs for non-conservative systems, the preliminary design guidelines of wave-like hybrid dampers are given through nonlinear modal analyses. The modal damping ratio and the nonlinear MEMCF are used to evaluate the damping generated by friction and piezoelectric mechanisms, respectively. The damping effect is also verified by steady-state response analyses through the Multi-Harmonic Balance Method (MHBM). By using a cantilever beam finite element (FE) model, the spatial distribution of piezoelectric material is optimized for a single wave-like hybrid damper. Four optimized hybrid dampers are then implemented to an industrial thin-walled structure. Taking the normal preload as an example, the influence of parameter distribution patterns at different interfaces on the damping effect is also discussed. Compared with the underlying friction damper, the wave-like hybrid damper not only provides greater damping, but is also less sensitive to the variation of excitation amplitude and the normal preload. Whether friction or piezoelectric damping is inactive, the proposed damper can still generate considerable damping.